Presentasi Diri Digital Dan Adaptasi Budaya Mahasiswa Perantau Universitas Negeri Jakarta Melalui Instagram - Khansa Syifaa; Maulina Larasati Putri; Vera Wijayanti Sutjipto; Marisa Puspita Sary; Sila Nirmala; Nur Rahmat (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
In today’s interconnected world, social media plays a vital role in how individuals build and display their identities, particularly among Generation Z. This study explores how migrant students employ Instagram’s multiple account features as a means of managing impressions, forming interpersonal connections, and navigating cultural adaptation. Drawing on Erving Goffman’s dramaturgy theory, the research examines frontstage and backstage behaviors within digital environments, highlighting how public and private expressions reflect broader cultural and emotional dynamics. Using a qualitative descriptive approach, data were gathered through in-depth interviews and digital content observation. The findings reveal that while public accounts reflect aspirational self-representations aimed at social validation, private spaces serve as emotional outlets that enable authenticity and interpersonal closeness. This demonstrates how digital platforms function as arenas for cultural negotiation and identity work, underscoring the interpersonal complexities of digital communication.